2021
DOI: 10.3390/jcm10215053
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative and Perioperative Predictors of Length of Hospital Stay after Primary Total Hip Arthroplasty—Our Experience on 743 Cases

Abstract: The aim of this retrospective investigation is to evaluate the correlation between several preoperative and perioperative factors and the length of hospital stay in patients that underwent elective total hip arthroplasty with overnight admission. Medical records of patients that underwent THA from the beginning of 2016 to the end of 2018 were retrospectively screened. Demographics, comorbidities, whole blood count, intraoperative details, and length of postoperative stay were retrieved. The association between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 38 publications
1
6
1
Order By: Relevance
“…ASA class and duration of surgery are indicators of the severity of surgical intervention and patient health status, and their associations with prolonged LOHS have been proven in previous studies. [39][40][41] In this study, we observed no significant relationship in terms of laboratory values with longer hospital stay. However, other reports have shown no direct evidence that elevated neutrophil counts are associated with poor prognosis.…”
Section: Discussioncontrasting
confidence: 67%
“…ASA class and duration of surgery are indicators of the severity of surgical intervention and patient health status, and their associations with prolonged LOHS have been proven in previous studies. [39][40][41] In this study, we observed no significant relationship in terms of laboratory values with longer hospital stay. However, other reports have shown no direct evidence that elevated neutrophil counts are associated with poor prognosis.…”
Section: Discussioncontrasting
confidence: 67%
“…IOPFF occurrence entailed a slight increase in the average LOS in comparison to that reported for primary THAs in the previous literature (5.81 vs. 4.00 days) [24]. Regardless, it is important to note that the calculation of LOS varies depending on the time of patients' admission (whether it is the night before the intervention or on the same day).…”
Section: Discussionmentioning
confidence: 73%
“…This study investigated the gait characteristics of patients who underwent THA one week after surgery, using EFA. Due to the increasing number of THA cases and escalating healthcare expenses, there is a pressing need to efficiently manage the process to enhance patient recovery, reduce complications, and shorten hospital stays [ 32 ]. In this context, clinical gait analysis can play a crucial role in identifying suitable candidates for early discharge and ensuring the quality of the recovery process.…”
Section: Discussionmentioning
confidence: 99%